Analysis of the cases of infection by Acinetobacter baumannii in intensive care units in Alagoas between 2014 and 2018 - Lemos, Isabella de Carvalho; Duprat, Irena Penha; Cavalcante de Melo, Géssyca; Melo de Oliveira, Janine; Gomes de Souza Maciel, Maria da Piedade (Revista Prevenção de Infecção e Saúde, 2023)
Introduction: The infection by Acinetobacter baumannii, an aerobic, gram-negative, ubiquitous coccobacillus, assumes endemic proportions with notable spread in Intensive Care Units. Aim: To analyze the cases of Acinetobacter baumannii infection in Adult Intensive Care Units in Alagoas between 2014 and 2018. Outlining: A transversal, descriptive and retrospective research was carried out with sample of 120 patients. Data collection was carried out through a questionnaire in the documents of two public hospitals in the city of Maceió-Alagoas, one of these is a referral in emergence and the other is referral in infectious diseases. Results: Of the 120 patients, 80 (66.7%) were from Hospital A and 40 (33.3%) from Hospital B. There was a prevalence of males (71.7%) and of the 18 to 40 age range (49.2%) in both hospitals. The antibiotic meropenem showed a higher frequency of use. Antimicrobial resistance and sensitivity profiles were higher for cephalosporins, carbapenems, and fluoroquinolones, as well as aminoglycosides, respectively. The most frequent bacterial isolation material was the tracheal secretion associated with mechanical ventilation. The most mentioned outcome was death. Implications: The study exposed high rates of mortality and antimicrobial resistance, as well as evidence that can contribute to the implementation of prophylactic measures for Acinetobacter baumannii.